2021
DOI: 10.3846/cibmee.2021.590
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of External Environment on Fintech Development

Abstract: Purpose – to propose an assessment tool of the environment of FinTech sector. Research methodology – systematic analysis of scientific literature has been carried out to form a methodology for FinTech sector environment assessment, which consists of quantitative methods used for the empirical research of the study as follows: PEST analysis, expert evaluation, determination of indicators’ values, normalization of data, multi-criteria assessment (the Simple Additive Weighting (SAW) method). Findings – the practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Multi-criteria assessment is done for the assessment of the FinTech PEST environment on a country level. For this step, 15 countries were selected to adopt a new FinTech PEST environment assessment tool (Pauliukevičienė & Stankevičienė, 2021). The composition of this tool is presented in Table 1 and the explanation of all indicators is provided in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-criteria assessment is done for the assessment of the FinTech PEST environment on a country level. For this step, 15 countries were selected to adopt a new FinTech PEST environment assessment tool (Pauliukevičienė & Stankevičienė, 2021). The composition of this tool is presented in Table 1 and the explanation of all indicators is provided in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the performance of each selected country in each environment, multi-criteria assessment (Simple Additive Weighting method) was used -every indicator was multiplied by its weight (Pauliukevičienė & Stankevičienė, 2021), and the numbers obtained after multiplication were summed in each environment (Appendix B). To assess the performance of each selected country in the overall PEST environment, the same principle was applied (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the Fintech industry can be stimulated by creating favorable external environment conditions at the national level (Pauliukevičienė & Stankevičienė, 2021a), but for the sustainable Fintech development, it is important to refine the interaction between the FinTech industry development and SDGs. Recent research has shown that there is a statistical link between the FinTech political, economic, social and technological (PEST) environment and SDG 4 "Quality Education", SDG 8 "Decent Work and Economic Growth", SDG 9 "Industry, Innovation and Infrastructure", SDG 16 "Peace, Justice and Strong Institutions", which suggests that FinTech PEST environment and SDG 4, SDG 8, SDG 9, SDG 16 are dependent (Pauliukevičienė & Stankevičienė, 2021b).…”
Section: Literature Reviewmentioning
confidence: 99%